LANGUAGE MODERNIZATION IN KAZAKH: TERMINOLOGY ISSUES - Maira Yessimzhanova (European Scientific Journal, ESJ, 2014)
Current globalization processes, technological updates and advancements in various fields of society leave different traces in languages. These changes are most noticeable in lexicon. One of the most important types of lexical changes is borrowings. To purify language from external influx a lot of substitutes have been introduced recently in the Kazakh language. This research aims to explore to what extent these new substitute words are understood by its speakers. Students participated in the study were asked to read short text from Kazakh Mass Media which included new substitutes for the previously existing borrowed words. They were asked to mark the words which they do not understand and suggest their possible meanings. The results demonstrate difficulties in understanding the new substitutes for the borrowed words.